2001
DOI: 10.1016/s0008-6215(01)00074-x
|View full text |Cite
|
Sign up to set email alerts
|

Transglucosidation of methyl and ethyl d-glucofuranosides by alcoholysis

Abstract: The acid catalyzed ethanolysis of methyl 5-O-methyl-alpha- and -beta-D-glucofuranoside and the analogous methanolysis of ethyl 5-O-methyl-alpha- and -beta-D-glucofuranoside have been investigated. For all four reactions, the primarily formed transglycosylation product was a single glycoside that had the opposite anomeric configuration to the starting material. This strongly indicates that a D-glucose methyl ethyl acetal is first formed and is then ring closed by a nucleophilic attack by HO-4, giving either the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…42, 43 These mechanistic conclusions were further refined by two recent studies on the acid-catalysed alcoholysis of methyl and ethyl 4-O-methyl-α-and β--glucopyranosides, 44 and of methyl and ethyl 5-O-methyl-α-and β--glucofuranosides. 45 In these two reports, Konradsson and co-workers show that the isomeric glycosides solvolyse by different mechanisms: pyranosides react via a D N ϩ A N exocyclic C-O cleavage, while the At the moment, it appears that the 2-hydroxy group is an important determinant for the mechanism of anomerisation. 46 Specifically, the results from a recent study of the acid-catalysed methanolysis of methyl 2-deoxy-β--arabino-hexopyranoside 47 suggest that for 2-deoxyglycopyranosides both exo-and endocyclic C-O bond cleavage mechanisms occur simultaneously, 46 although at the present time it is not clear whether the ringopening pathway occurs with or without nucleophilic solvent participation.…”
Section: Acid-catalysed Reactions In Other Solventsmentioning
confidence: 99%
“…42, 43 These mechanistic conclusions were further refined by two recent studies on the acid-catalysed alcoholysis of methyl and ethyl 4-O-methyl-α-and β--glucopyranosides, 44 and of methyl and ethyl 5-O-methyl-α-and β--glucofuranosides. 45 In these two reports, Konradsson and co-workers show that the isomeric glycosides solvolyse by different mechanisms: pyranosides react via a D N ϩ A N exocyclic C-O cleavage, while the At the moment, it appears that the 2-hydroxy group is an important determinant for the mechanism of anomerisation. 46 Specifically, the results from a recent study of the acid-catalysed methanolysis of methyl 2-deoxy-β--arabino-hexopyranoside 47 suggest that for 2-deoxyglycopyranosides both exo-and endocyclic C-O bond cleavage mechanisms occur simultaneously, 46 although at the present time it is not clear whether the ringopening pathway occurs with or without nucleophilic solvent participation.…”
Section: Acid-catalysed Reactions In Other Solventsmentioning
confidence: 99%
“…Nucleophilic substitution reactions for most acetals (R′O–CHR–OR′′), which contain few electron-withdrawing groups, generally proceed via discrete oxacarbenium ion intermediates (S N 1 mechanisms) due to stabilization of positively charged species by the second oxygen atom. In contrast, nucleophilic substitution reactions on carbohydrate acetal linkages straddle the mechanistic border between S N 1 and S N 2 reactions by virtue of the inherently short lifetimes of oxacarbenium ion intermediates; as a result, reactions via ion-pairs become important . For instance, in water the glucopyranosylium ion has an estimated lifetime of approximately 1–3 ps. , In addition, studies have shown that, during alcoholysis of alkyl furanosides, cyclic oxacarbenium ions are not intermediates (these reactions involve a concerted S N 2 ring-opening mechanism). …”
mentioning
confidence: 99%
“…Acidification of an ethanol solution produces a reaction environment that allows the esterification of cellulose. The esterification of cellulose with ethanol can produce an ethyl-glucoside product that first degrades to become 5-hydroxymethylfurfural and then further degrades to myriad other compounds in an ethanol environment 31 , 32 , 44 , 45 . However, this reaction has not been shown to occur in a whiskey solution.…”
Section: Discussionmentioning
confidence: 99%